Developing a Case-Based General Biology Textbook Using the ADDIE Model to Enhance Conceptual Understanding of Undergraduate Science Education Students - Rizka Elan Fadilah; Ika Dewi Sumiati; Siti Shofa Assyifa’ul Qulbi Barid; Liu Hsiu Chen (Jurnal Pendidikan Sains Indonesia, 2026)
Biology textbooks that are most frequently employed in Jember University are often not very contextual for students because the topics covered are not related to familiar concepts. This study aims to ascertain the validity, effectiveness, and practicality of a case-based general biology textbook developed using the ADDIE model. The study was conducted during the first semester of the 2025/2026 academic year. The study employs a developmental research approach, utilizing the ADDIE model, which comprises five distinct stages: analyze, design, develop, implement, and evaluate. The validity test employed a validity questionnaire, the effectiveness test utilized pretests and post-tests, and the practicality test employed a practicality questionnaire. The study's findings suggest that the case-based general biology textbook developed is highly valid, with an overall score of 92.3%. A comprehensive evaluation of the textbook's efficacy was conducted, utilizing a pre- and post-test approach. The analysis indicated that the textbook demonstrated a moderate degree of effectiveness in enhancing students' conceptual understanding, as evidenced by an N-gain value of 0.45, which classified it within the moderate category. The results of the practicality test further confirmed the textbook's practicality, with a score of 91.5%. This study concludes that the case-based general textbook developed using the ADDIE model is proven to be valid, effective, and practical for improving students' conceptual understanding